MAPPING ARCHIVAL RESEARCH AT THE SCHOOL OF LIBRARY AND INFORMATION STUDIES (SLIS), UNIVERSITY OF THE PHILIPPINES: IMPLICATIONS FOR CURRICULUM DEVELOPMENT - Golfo, Mary Grace P. (Journal of Philippine Librarianship; Vol 35 (2015): A-LIEP 2015 Special Issue, 2016)
Elective courses in archival studies have been offered as part of the Library and Information Science Program course offering of the School of Library and Information Studies as early as 1954. Although, research on the field only started in 1978, a total of sixty-six (66) studies on archives and records management related topics were already conducted by both the graduate and undergraduate students as of 2014. This paper looks into the typology of research done by students both in the graduate and undergraduate levels and use it as one component in the identification of the areas which need to be considered in the development of a graduate curriculum in Archival Studies.
Keywords: archival studies, archives research, research typology